ANTICANCER ACTIVITY OF ETHANOL EXTRACT OF POLYCARPAEA CORYMBOSA (L.) LAM WHOLE PLANT AGAINST DALTON ASCITES LYMPHOMA - K.BALAMURUGAN; A.NISHANTHINI; V.R.MOHAN (International Journal of Pharma and Bio Sciences, 2013)
The present study aims to evaluate the antitumor activity of ethanol extract of whole plant of Polycarpaea corymbosa on DAL model in Swiss Albino miceThe following parameters: tumor volume, viable and non viable cell count and life span of host were evaluated DAL bearing in swiss albino mice. The above said parameter were also evaluation by administrating ethanol extract of whole plant of Polycarpaea corymbosa. The results showed a decrease in tumor volume and cell viability. Hematological studies revealed that, the Hb count decreased in DAL treated mice, whereas, it was induced by the drug treated animals and showed an increase in Hb near to normal levels. The results suggested that, the extracts of whole plant of Polycarpaea corymbosa exhibited significant antitumor activity on DAL bearing mice.